Antioxidant and Antimicrobial Properties of Cactus Pear (Opuntia) Seed Oils - Esther Ramírez-Moreno; Raquel Cariño-Cortés; Nelly del Socorro Cruz-Cansino; Luis Delgado-Olivares; José Alberto Ariza-Ortega; Vanessa Yelina Montañez-Izquierdo; María Manuela Hernández-Herrero; Tomás Filardo-Kerstupp (Journal of Food Quality)
Seed oils from two Mexican varieties of cactus pear (green: Opuntia albicarpa and red: Opuntia ficus indica) were extracted with different solvents (hexane, ethanol, and ethyl acetate) to evaluate their antioxidant activity. The seed oil with higher antioxidant activity was selected to evaluate antimicrobial activity. The fatty acid profile was analyzed by gas chromatography-mass spectrometry (GC-MS). Oil from green cactus pear seeds obtained with ethanol and ethyl acetate exhibited higher antioxidant activity (p<0.05) of 323 and 316 μmol TE/20 mg (p < 0.05), respectively, compared to red cactus pear seed oil (≈274 and 247 μmol TE/20 mg with ethyl acetate and ethanol, resp.). The oil obtained with ethanol and higher antioxidant activity was used to determine the antimicrobial activity. Both cactus pear oils produced a microbial inhibition zone in most of the microorganisms evaluated, particularly Saccharomyces cerevisiae which had similar diameter (38–40 mm). The oil fatty acids profiles of both varieties were similar and exhibited a high content of linoleic acid, while two fatty acids (linolenic and behenic) found in red cactus pear were not observed in the green variety.